A desregulamentação e o desempenho do complexo sucroalcooleiro no Brasil. - Baccarin, José Giacomo (2005)
This work analyzed the evolution of the relation between the sugar and alcohol complex and the State from 1975 to 2002, when there was a change from public intervention, marked by Proálcool , to a new situation, in which deregulation is proposed. We attempted to interpret the main political and economical stipulators of the process, as well as describe the way it happened and how the structure and performance of the process were affected. It is assumed that since 1985 the possibilities of an orchestration of social and economical interests allowing the maintenance of a national, public and continuous program to support the sugar and alcohol complex have narrowed. The financial crisis of the Brazilian State and the adoption of liberal politic orientation, the prevailing conditions of the oil market and the resistance of Petrobrás to the increase of alcohol production have contributed to this situation, as well as the little interest of car makers to develop ethanolpowered engines in the 1990 s. It is also assumed that the political pressure strength of sugar and alcohol complex representatives and the specific formal relations established with the federal administrative machine throughout decades have made the sugar and alcohol deregulation differentiated and marked by compensation policies. From 1975 to 1985, the complex counted on favored public policies that resulted in great increase of the production capacity, consumption and production of fuel ethanol. Since 1986, the price fixation policy for sugar and alcohol products was more unfavorable, resulting in production settling until 1990. The extinction of the Sugar and Alcohol Institute (IAA), in 1990, formally gave birth to deregulation, marked by constant tension between government and millers. The elimination of the public monopoly on sugar exportation and the defrosting of sugarcane, sugar and alcohol prices in 1999 are noticeable. In compensation, the addition of 20% to 24% of anhydrous ethanol to gasoline became obligatory; the gasoline was overtaxed in benefit of alcohol, and a specific source of production and buildup financing for sugar and alcohol was created. From 1990 to 2002, while alcohol production remained still, there was an increase of sugar production aiming the world market. Crop and industry yield did not show higher increase with deregulation. However, the work productivity did. The sugarcane production tended to concentrate in the centersouth, instead of the north-northeast. There was a considerable decrease in the number of mills, but the remaining became bigger. It can be concluded that in fact there was no complete deregulation, but actually a change resulting in a new regulation. We suggest that the public intervention should not be attached to opportunist interests, but a public/private agenda that contributes to the maintenance of the complex and guarantees alcohol supply to the society as an energy source.